KORELASI KETERAMPILAN PROSES SAINS DENGAN HASIL BELAJAR MAHASISWA PADA PRAKTIKUM KIMIA DASAR II ( KINETIKA REAKSI) - Khery, Yusran; Pahriah, Pahriah; Jailani, Abdul Kadir; Rizqiana, Abu; Iswari, Nurma A. (Hydrogen: Jurnal Kependidikan Kimia, 2019)
The aim of this research was to evaluate correlation between students science process skill and learning achievement. In form of correlation research, this research was conducted at Chemestry Laboratory of IKIP Mataram in time of 2015-2018. Subject of this researh consists of 138 students who got basic II chemistry practice. Instrument of this research was guestionnaire and test. With 98,22% of validity, the instrument was highly eligible to used in data collecting. The data analyzed by product moment. The data analysis showed that rtest (0,1743) higher than rtable (0,1676). The research showed that there is significant correlation betwen science process skills and students learning achievement.